2020
DOI: 10.1002/chem.201905339
|View full text |Cite
|
Sign up to set email alerts
|

Compressing a Non‐Planar Aromatic Heterocyclic [7]Helicene to a Planar Hetero[8]Circulene

Abstract: This work describes as ynthetica pproachw here an on-planar aromatic heterocyclic [7]helicene is compressedt oy ield ah etero[8]circulene containing an inner antiaromatic cyclooctatetraene (COT) core. This [8]circulene consists of four benzene rings and four heterocyclic rings, and it is the first heterocyclic[ 8]circulenec ontaining three differenth eteroatoms. The synthetic pathway proceeds via at he flattened dehydro-hetero[7]helicene, which is partially ah elicene and partially ac irculene:i ti s non-plana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…[27] The diazathia [7]helicene motif has been reported to racemise readily at room temperature. [32] The new peak at 327 nm induced by L2 in the VTCD experiment with h-telo in Na + has am elting temperature of 14.2 8C. We consider this av alid estimation for the helicene racemisationb arrier, as the interaction between DNA and helicene ligand L2 is non-stabilising.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…[27] The diazathia [7]helicene motif has been reported to racemise readily at room temperature. [32] The new peak at 327 nm induced by L2 in the VTCD experiment with h-telo in Na + has am elting temperature of 14.2 8C. We consider this av alid estimation for the helicene racemisationb arrier, as the interaction between DNA and helicene ligand L2 is non-stabilising.…”
Section: Resultsmentioning
confidence: 96%
“…For this study, we use two hetero[7]helicene ligands: L1 and L2 . The helicene ligands obey many of the criteria described above (aromatic, hydrophobic and positively charged ammonium groups), but in contrast to previously studied ligands, the P ‐ and M ‐enantiomers of these helicene ligands interconvert rapidly at room temperature, [28, 31, 32] and consequently both of the two enantiomers are readily available for selective recognition of the G‐quadruplexes. We have found that these helicene ligands stabilise parallel k‐ras G‐quadruplexes and convert polymorphic h‐telo structures into conformations with increased parallel character.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations